A change of scale formula for Wiener integrals on abstract Wiener spaces - Il Yoo; David Skoug (International Journal of Mathematics and Mathematical Sciences)
In this paper we obtain a change of scale formula for Wiener integrals on abstract Wiener spaces. This formula is shown to hold for many classes of functions of interest in Feynman integration theory and quantum mechanics.